m5C regulator-mediated modification patterns and tumor microenvironment infiltration characterization in colorectal cancer: One step closer to precision medicine - Chen, Baoxiang; Xi, Yiqing; Zhao, Jianhong; Hong, Yuntian; Tian, Shunhua; Zhai, Xiang; Chen, Quanjiao; Ren, Xianghai; Fan, Lifang; Xie, Xiaoyu; Jiang, Congqing (Frontiers in Immunology, 2022)
Abstract Background: The RNA modification 5-methylcytosine (m5C) is one of the most prevalent post-transcriptional modifications, with increasing evidence demonstrating its extensive involvement in the tumorigenesis and progression of various cancers. Colorectal cancer (CRC) is the third most common cancer and second leading cause of cancer-related deaths worldwide. However, the role of m5C modulators in shaping tumor microenvironment (TME) heterogeneity and regulating immune cell infiltration in CRC requires further clarification. Results: The transcriptomic sequencing data of 18 m5C regulators and clinical data of patients with CRC were obtained from The Cancer Genome Atlas (TCGA) and systematically evaluated. We found that 16 m5C regulators were differentially expressed between CRC and normal tissues. Unsupervised cluster analysis was then performed and revealed two distinct m5C modification patterns that yielded different clinical prognoses and biological functions in CRC. We demonstrated that the m5C score constructed from eight m5C-related genes showed excellent prognostic performance, with a subsequent independent analysis confirming its predictive ability in the CRC cohort. Then we developed a nomogram containing five clinical risk factors and the m5C risk score and found that the m5C score exhibited high prognostic prediction accuracy and favorable clinical applicability. Moreover, the CRC patients with low m5C score were characterized by “hot” TME exhibiting increased immune cell infiltration and higher immune checkpoint expression. These characteristics were highlighted as potential identifiers of suitable candidates for anticancer immunotherapy. Although the high m5C score represented the non-inflammatory phenotype, the CRC patients in this group exhibited high level of sensitivity to molecular-targeted therapy. Conclusion: Our comprehensive analysis indicated that the novel m5C clusters and scoring system accurately reflected the distinct prognostic signature, clinicopathological characteristics, immunological phenotypes, and stratifying therapeutic opportunities of CRC. Our findings, therefore, offer valuable insights into factors that may be targeted in the development of precision medicine-based therapeutic strategies for CRC. Keywords: 5-methylcytosine; RNA methylation; Colorectal cancer; Immune infiltrates; Tumor microenvironment; Precision medicine